Pengaruh Kurs, Suku Bunga BI Rate, Harga Minyak Dunia terhadap Indeks Harga Saham LQ45 Periode Januari 2012-Desember 2014 - Ratih, Dewi, Didit Purnomo, SE. MSi (2016)
This study entitled "Influence Kurs, interest rate BI rate and world oil prices Against Stock Price Index LQ45 period January 2012 - December 2014". The purpose is to determine the effect of exchange rates, the SBI rate and world oil prices towards LQ45 period January 2012 - December 2014. The data used in this research is secondary data in the form of monthly time series. The analytical tool used in this research is multiple linear regression. From the results it can be concluded that stationary analysis test results showed that the variable rate and BI rate negative effect on the stock price index LQ45, the world oil price variable does not affect the stock price index LQ45. In the classical assumption there is no problem heteroscedasticity in the model and the test autocorrelation there is no autocorrelation in the model, the normal Ut distribution normality test and the test specification model (Ramsey Research) linear model analysis model specification benar. Ujiit is known that variable rate and BI rate significantly negative effect on the stock price index LQ45 variable while world oil prices do not affect the stock price index LQ45